Guru Tasawuf á¸¤aá¸rat al-Shaykh K.H. M. Hasyim Asyâ€™ari di Makkah: Menyelisik Catatan C. Snouck Hurgronje tentang Syekh â€˜Abd al-ShakÅ«r Surabaya - Karyadi, Fathurrochman (Fakultas Agama Islam, Universitas Hasyim Asy'ari, 2021)
This article will answer a question who is the Sufism teacher á¸¤aá¸rat al-Shaykh Hasyim Asyâ€™ari in Makkah? To answer this question, the writer uses primary and secondary data. The first is primary data, the author is guided by the manuscript in the book of á¸¤aá¸rat al-Shaykh's legacy. A philological approach is needed to read it. While the second is secondary data, the author refers to Snouck Hurgronje's writing which records the activities of the hajj, especially the Javanese community in Mecca. In this study, the authors found data on the name of Syekh â€˜Abd al-ShakÅ«r Surabaya as á¸¤aá¸rat al-Shaykh's teacher in the field of Sufism along with some information related to the teacher that is not often found in the existing literature.